O'Hara's choice : a novel - Uris, Leon, 1924-2003 (HarperCollinsPublishers, 2003)
In the years following America's terrible Civil War, the fate of the U.S. Marine Corps rests in the capable hands of Zachary O'Hara. A first-generation Irish-American and son of a legendary war hero, O'Hara is the one man who can prevent the dissolution of his father's beloved "Wart-Hogs," thereby ensuring his own future as a valuable member of this proud and vital branch of his nation's armed forces. But a dark secret weighs heavily on this tormented, dedicated warrior. And the greatest obstacle to his mission is one he never anticipated: Amanda Blanton Kerr, the passionate, obstinate daughter of the ruthless industrialist who's the Corps' fiercest adversary. A beautiful heiress on a mission of her own, her destiny will intertwine with O'Hara's in the tumultuous decades to follow, forcing him to confront the devastating choice no soldier should ever have to make: between his duty and his desire; between his country and his heart.